(untitled) (Physical Education, Health and Social Sciences, 2025)
Outcomes-Based Education (OBE) is an innovative educational reform that prioritizes learners by ensuring that curriculum design, instruction, and assessments align with clearly defined outcomes. While OBE has been widely implemented in secondary and higher education, its use in early childhood education (ECE) in Pakistan has yet to be systematically explored, despite the country’s reliance on play-based and culturally relevant pedagogies in preschool education. This research protocol is based on a pre-pilot study and situational validation conducted at the Frontier Children Academy (FCA), a prominent private school in Peshawar. Insights from the pilot phase helped refine the conceptual framework, data collection tools, and observation protocols, paving the way for evaluating a feasible OBE-informed preschool model. The study will adopt a qualitative single-case design to examine the interpretation, implementation, and contextual suitability of OBE at FCA, chosen for its diverse student population and commitment to integrating curriculum, pedagogy, and assessments. Using Spady’s OBE framework, Bronfenbrenner’s ecological systems theory, and constructivist learning theory, data will be collected through semi-structured interviews, classroom observations, focus group discussions, and document analysis. Analysis will follow the six steps of thematic analysis by Braun and Clarke. This research aims to provide context-specific evidence that supports the implementation of outcome-oriented practices in preschool education while preserving developmental relevance, play-based learning, and cultural responsiveness in Pakistan.